G249 Healthcare crowdfunding in the UK and australia: benefits and ethical concerns. (May 2019) - Aylett, SE; Moore, B; Gillam, L
Abstract : Aims: To conduct empirically informed, ethical analysis of cases of healthcare crowdfunding in children. Methods: 20 sequential Australian and 20 UK cases on 'GoFundMe' were compiled. The following data were recorded: demographics, diagnosis, goals of the fundraising campaign, the campaign duration, number of updates, the total sum raised and whether confidential medical information about the child was posted. Results: Most campaigns were started by friends or relatives (84% Australian, 55% UK). The most frequent goals were for local treatment not funded by the government (50% Australian, 25% UK), treatment abroad (20% Australian, 15% UK) and financial support for the parents taking time off work to be with their child (45% Australian, 50% UK). The average duration of campaign was 16.6 months (Australian), 17.5 months (UK). The total average funds raised per campaign were 89, 771AUD and £20 081. Campaigns concerned a range of diagnoses, including tumours, genetic conditions, cerebral palsy, accidental or non-accidental injuries, infections, prematurity and inflammatory conditions. In one case, parents sought to raise funds for IVF for a 'saviour sibling' for a child needing bone marrow transplant. All parents expressed gratitude for the support they received, which emotionally and practically benefitted families and allowed some children to access treatment otherwise not available. Updates were often written as a detailed diary of the child's illness and progress, disclosing confidential information. Photos showed children attached to medical equipment (35% Australian, 43% UK), with some ventilated on PICU, including a competent 15-year-old. In 20% of Australian and UK cases, the child's body (torso or chest) was exposed. Conclusions: Healthcare crowdfunding for children can benefit children and families. There are similarities and differences in campaigns for Australian and UK children. Australian families more often seek funding for medical bills and specialist treatment not otherwise available. However, crowdfunding raises ethical issues in relation to the child's confidentiality, the future impact of medical information being publicly shared on children who survive, and the broader ethical issue of equity of access for those unable to crowdfund for their child.